Lysyl oxidase mediates hypoxia-induced radioresistance in non-small cell lung cancer A549 cells. Issue 4 (February 2016) - Gong, Chongwen; Gu, Runxia; Jin, Honglin; Sun, Yao; Li, Zhenyu; Chen, Jing; Wu, Gang
Hypoxia-induced radioresistance has been well known as the main obstacle in cancer radiotherapy. Lysyl oxidase (LOX) was previously demonstrated to play an important role in hypoxia-induced biological behaviors, such as metastasis and angiogenesis, through hypoxia-inducible factor-1α (HIF-1α), which is an important contributing factor to radioresistance in tumor cells. However, how LOX plays a role in hypoxia-induced radioresistance has yet to be determined. Here, we found that LOX expression was in accordance with HIF-1α expression, and LOX expression at the mRNA and protein level, and enzymatic activity were remarkably upregulated in the hypoxic A549 cells, compared with normoxic A549 cells. Inhibition of LOX resulted in the reduction of the ability to repair double-stranded breaks (DSBs), promotion of apoptosis, relief of G2/M cycle arrest, and eventually reduction of hypoxia-induced radioresistance in the hypoxic A549 cells. This suggests that LOX may play an important role in hypoxia-induced radioresistance. Together, our results might suggest a novel potential therapeutic target in the management of non-small cell lung cancer (NSCLC).